VHF and microwave radiation emitted by lightning and its effect towards 4G LTE wireless communication - Shamsul Baharin, Shamsul Ammar (2024)
Electric breakdown process starts with electron avalanche, and then streamer and lastly become leader. They initiate almost all types of lightning flashes except narrow bipolar event (NBE) that was believed to be initiated by fast breakdown. This thesis explores the temporal characteristics of microwave and very high frequency (VHF) electric field radiations associated with the conventional breakdown of stepped leader pulses (SLPs) from negative cloud-to-ground (-CG) flash and fast breakdown of NBEs. The primary motivation is to discern whether both microwave and VHF radiations emitted from the same process or originated from different sources. In existing literature, propagating streamers are identified as the source of VHF radiation emission, while microwave radiation from lightning resulted from head-on collisions of streamers and electron avalanche/corona breakdown at the tip of the leader. Considering that The Fourth Generation Long Term Evolution (4G LTE) mobile links operate in the microwave band, potential interference effects during data transmission need to be investigated as lightning also radiated well at microwave band. To address these objectives, three different measurement setups were designed. First, an experimental setup consisted of fast and slow-varying antennas and radio sensors to capture the temporal characteristics of microwave and VHF radiation associated with SLPs and NBEs. Additionally, a VHF interferometer was implemented to observe the direction and propagation of velocities as well as the altitude height of the VHF radiation sources of NBEs. Furthermore, the study integrated measurements of lightning electric field and 4G LTE performance to assess potential interference effects during data transmission. The noteworthy findings of this study reveal that the sources of microwave and VHF radiation associated with both electrical breakdowns originate from different sources, as evidenced by the temporal analysis of the onset time differences. Further analysis indicates that positive NBEs exhibited a 46% bigger for onset time difference between microwave radiation and VHF emissions, compared to SLPs. In contrast, negative NBEs demonstrated an even more remarkable 85% bigger in the same context. Moreover, when examining the VHF radiation associated with positive and negative NBEs in relation to the onset of fast electric field, positive NBEs displayed a 62% bigger compared to SLPs while negative NBEs exhibited an astonishing 88% bigger. These results suggest that the speed of electron avalanches and streamers of fast breakdown of NBEs is faster compared to the conventional electron avalanches and streamers of SLPs. Additionally, the VHF interferometer mapping reveals that the VHF radiation sources for NBEs propagate bidirectionally with a propagation speed reaching 108 ms-1. After comparing the performance of 4G LTE data transmission in both fair weather and thunderstorms, minimal impact was observed during fair weather. However, disruptions were reported during three reported thunderstorms, affecting either the client or server nodes. Furthermore, -CG and intra-cloud (IC) flashes were identified as the main factors that interrupted the data transmission.